Pengaruh Digital Marketing dan Sertifikasi Halal Terhadap Pendaptan Pelaku Usaha Mikro Kecil dan Menengah Bidang Kuliner di Kebonsari, Madiun - Safitri, Wahyu Dyan (TAZKIA JURNAL, 2024)
MSME actors must be able to take advantage of changes that occur in their business environment, including digital marketing, to apply it to the businesses they run. The culinary sector of MSME also need to pay attention to the importance of halal certification. Halal certified food products provide very promising opportunities for business sustainability. The aim of this research is to examine and analyze the influence of digital marketing and halal certification partially or simultaneously on the income of MSMEs in the culinary sector in Kebonsari District, Madiun Regency. The research population was 375 MSME actors in the culinary sector in Kebonsari District, Madiun Regency. The number of samples was determined using the Slovin formula, 80 MSME actors in the culinary sector were obtained as samples determined using a purposive sampling technique. Research data was collected using a questionnaire and analyzed using multiple linear regression analysis. The research results show that digital marketing and halal certification partially have a positive and significant effect on the income of MSMEs in the culinary sector in Kebonsari District, Madiun Regency. Digital marketing and halal certification simultaneously influence the income of MSMEs in the culinary sector in Kebonsari District, Madiun Regency.